The Development of The Tahfiz Al-Quran At-Tanwīr. Method at Tahfiz Al-Quran Islamic Boarding School Muhammadiyah Ibnu Juraimi Yogyakarta - Thohari Rohman, Charis; Bashori, Khoiruddin; Samsudin, Muh. (Devotion : Journal of Research and Community Service, 2022)
Tahfiz is very closely related to cognitive processes that involve memory. Process, store and retrieve knowledge or information when needed. Today, educational institutions that make tahfiz a massive flagship program have emerged. This type of research is research and development which aims to: 1) Determine the needs of the students of the Tahfiz al-Quran Muhammadiyah Islamic Boarding School Ibnu Juraimi Yogyakakarta for the tahfiz al-Quran at-Tanwīr method. 2) Knowing the steps for developing the Tahfiz al-Quran at-Tanwīr method at the Tahfiz al-Quran Muhammadiyah Islamic Boarding School, Ibnu Juraimi, Yogyakarta. 3) Knowing the advantages and disadvantages of the tahfiz al-Quran at-Tanwīr method. Researchers collected data using interview, questionnaire, observation, and documentation techniques. The conclusions of this study are: 1) The results of needs analysis and problem identification indicate the need to develop the tahfiz al-Quran at-Tanwīr method at the Tahfiz al-Quran Muhammadiyah Islamic Boarding School Ibnu Juraimi Yogyakarta. 2) Globally, the steps for developing the tahfiz al-Quran at-Tanwīr method are divided into 3, namely: Operational instructions for success requirements, operational instructions for implementation, and operational instructions for guarding. 3) The advantages of the tahfiz al-Quran at-Tanwīr method are that it provides convenience and a strong initial foundation for memorizing the Koran, facilitates tadabbur and knows the location, number, waqf, and meaning, and writing verses so that it is hoped that it will facilitate the cultivation of quranic characters. While the shortcomings of the tahfiz al-Quran at-Tanwīr method are: The ability to understand and store heterogeneous student information, the duration of time is longer, and the delivery of information must attract the attention of students.